2021
DOI: 10.1097/scs.0000000000007485
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of Different Spreader Techniques in Primary Open Septorinoplasty in Terms of Nasal and Olfactory Functions

Abstract: Background: In this study, the authors aimed to investigate the use of spreader and determine the efficacy and superiority of different spreader techniques in septorhinoplasty in terms of nasal and olfactory functions. Methods: A total of 60 patients who had undergone septorhinoplasty with the open technique were included in the study. In addition to open septorhinoplasty, 20 patients also underwent bilateral spreader graft placement and 20 bilateral spreader flap placement. For the remaining 20 patients, open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…This investigation demonstrated that bilateral spreader grafts produce a significantly higher increase of PNIF when compared to spreader flaps, to a combination of spreader flaps plus a unilateral spreader graft or to none of these (Figure 1). Though being expected from their effect on nasal valve widening, the functional role of spreader grafts has not consensus, with some studies demonstrating an improvement of nasal breathing [30][31][32] while other studies could not demonstrate consistent functional benefits. 20,[33][34][35][36] Modifications of spreader grafts have been proposed to improve their functional effect 37,38 and additional techniques, such as the flaring suture 39 or the splay graft 40 have been suggested for the same purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation demonstrated that bilateral spreader grafts produce a significantly higher increase of PNIF when compared to spreader flaps, to a combination of spreader flaps plus a unilateral spreader graft or to none of these (Figure 1). Though being expected from their effect on nasal valve widening, the functional role of spreader grafts has not consensus, with some studies demonstrating an improvement of nasal breathing [30][31][32] while other studies could not demonstrate consistent functional benefits. 20,[33][34][35][36] Modifications of spreader grafts have been proposed to improve their functional effect 37,38 and additional techniques, such as the flaring suture 39 or the splay graft 40 have been suggested for the same purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Zeid et al 41 compared nasal airway resistance before and after rhinoplasty using spreader flaps or spreader grafts and concluded that both techniques decreased nasal airway resistance without significant difference between the 2 techniques. Sowder et al 42 and Bilgin et al 31 also compared the functional effect of spreader flaps and spreader grafts using NOSE score and found no significant difference between the 2 techniques. The results of our investigation do not corroborate these studies, as the functional effect of spreader grafts was significantly higher than the effect of spreader flaps.…”
Section: Discussionmentioning
confidence: 99%